Phenological development of East African highland banana involves tradeoffs between physiological age and chronological age - Taulya, Godfrey; Asten, Piet J.A. van; Leffelaar, P.A.; Giller, Kenneth E. (Elsevier, 2014)
The phenology of East African highland banana (Musa acuminata AAA-EA, hereafter referred to as ‘high-land banana’) is poorly understood. We tested three hypotheses: (1) the physiological age at floweringis independent of site effects, (2) there is no difference in threshold size at flowering between sites withdifferent growth potential, and (3) morphological and physiological components of highland banana rel-ative growth rate (RGR) contribute equally to mitigate growth reduction in response to limiting supplyof water, K or N. The physiological age of highland banana plants from field trials at Kawanda (centralUganda) and Ntungamo (south-western Uganda) was computed from daily temperature records. Growthanalysis was conducted using RGR, net assimilation rate (NAR), specific leaf area (SLA) and leaf mass ratio(LMR) estimated from allometry. Growth response coefficients were used for quantifying the relativecontribution of NAR, SLA and LMR to RGR. Physiological age at flowering was delayed by 739?C d atKawanda compared with that at Ntungamo whose chronological age at flowering was in turn 51 d older.At both sites a threshold total dry mass of 1.5 kg per plant was required for flowering. Faster absolutegrowth rate and NAR fostered by wet conditions, K input and cooler temperatures enabled plants atNtungamo to attain the threshold total dry mass sooner than those at Kawanda, hence the phenotypicplasticity in age at flowering. Net assimilation rate contributed at least 90% to RGR increase due to wetconditions at both sites. The contribution of NAR to RGR increase in response to K at Kawanda reducedto 38% while that for SLA increased to 49%. Net assimilation rate contributes more to highland bananaRGR modulation than SLA except when warmer conditions reduce NAR. Differences in crop growth ratecause phenotypic plasticity in highland banana rate of phenological development.